Comparative Genomics for Evolutionary Cell Biology Using AMOEBAE: Understanding the Golgi and Beyond - Barlow, Lael D; Maciejowski, William; More, Kiran; Terry, Kara; Vargová, Romana; Záhonová, Kristína; Dacks, Joel B (Methods in molecular biology (Clifton, N.J.), 2023)
Taking an evolutionary approach to cell biology can yield important new information about how the cell works and how it evolved to do so. This is true of the Golgi apparatus, as it is of all systems within the cell. Comparative genomics is one of the crucial first steps to this line of research, but comes with technical challenges that must be overcome for rigor and robustness. We here introduce AMOEBAE, a workflow for mid-range scale comparative genomic analyses. It allows for customization of parameters, queries, and taxonomic sampling of genomic and transcriptomics data. This protocol article covers the rationale for an evolutionary approach to cell biological study (i.e., when would AMOEBAE be useful), how to use AMOEBAE, and discussion of limitations. It also provides an example dataset, which demonstrates that the Golgi protein AP4 Epsilon is present as the sole retained subunit of the AP4 complex in basidiomycete fungi. AMOEBAE can facilitate comparative genomic studies by balancing reproducibility and speed with user-input and interpretation. It is hoped that AMOEBAE or similar tools will encourage cell biologists to incorporate an evolutionary context into their research.
Keywords: Basidiomycete; Golgi; Molecular evolution; Amoeba; Biological Evolution; Evolutionary Cell Biology; genomika; BLAST; Homology searching; Adaptin; Workflow; výpočetní biologie; reprodukovatelnost výsledků; Computational Biology; Computational pipeline; Reproducibility of Results; Golgi Apparatus; Golgiho aparát; Comparative genomics; biologická evoluce; Genomics